1995
DOI: 10.1557/proc-413-577
|View full text |Cite
|
Sign up to set email alerts
|

Electrically Conducting Polymer Blends Based On Polyaniline

Abstract: Polyaniline offers a promissing possibility to make electrically conducting polymer blends with tailorable surface and bulk conductivities. The matrix polymer can be a thermoplast or a thermo- set. Different commonly used polymer processing methods are applicable to the blends; e.g. injection moulding, film blowing, compression moulding and fiber spinning. Also commonly used thermoset resins processings are possible. The key feature in making all this feasible is the co- solvent/plasticizer technology develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…In some cases, the volume and surface resistivities of polymers are much higher than are ordinarily required. It is melt processable and it can be blended with many thermoplastics such as polypropylene (PP), polyethylene (PE), polystyrene (PS), and polyvinyl chloride (PVC) [8][9][10] . Humidity affects volume resistance of different insulators to markedly different extents.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, the volume and surface resistivities of polymers are much higher than are ordinarily required. It is melt processable and it can be blended with many thermoplastics such as polypropylene (PP), polyethylene (PE), polystyrene (PS), and polyvinyl chloride (PVC) [8][9][10] . Humidity affects volume resistance of different insulators to markedly different extents.…”
Section: Introductionmentioning
confidence: 99%
“…1 Shacklette et al 1 reported that blends of Versicon™ (Allied-Signal Inc.), a conductive form of PANI, and polar polymers exhibited a conductivity threshold in a range of 6 -10 wt % Versicon™. Ikkala et al [2][3][4] reported that conductive polymer blends, prepared by conventional melt blending of a variety of thermoplastic polymers with a Neste PANI complex (Neste Oy, Finland), could be processed by ordinary methods, such as injection molding, film blowing, and fiber spinning. They emphasized that the key factor in their processing studies was a plasticizer technology developed by Neste Oy.…”
Section: Introductionmentioning
confidence: 99%
“…Among ICPs, polyaniline (PANI) is one of the most intensively investigated materials. It is melt processable and it can be blended with many thermoplastics, such as polypropylene (PP), polyethylene (PE), polystyrene (PS) and poly(vinylch1oride) ( W C ) (9)(10)(11)(12). PANI has a semi-rigid backbone and is nearly impossible to melt process without a plasticizer.…”
Section: Introductionmentioning
confidence: 99%
“…The suitable plastncizing additive (e.g. additional amount of protonating agent, such a s dodecyl benzene sulphonic acid, DBSA) allows that conductive PANI networks can be formed in non-polar matrix polymers (10)(11)(12). The blend conductivity depends on many factors such as the weight fraction of the plasticized PAM-complex, the level of the plasticizer within the PANI-complex, the processing temperature and shear stress applied, the viscosity of the matrix polymer, and the surface activity of the PANI-complex.…”
Section: Introductionmentioning
confidence: 99%